The effect of disclosure regulation on the bias and accuracy of management earnings forecasts in Malaysian IPO prospectuses - Ammer, Mohammed Abdullah; Ahmad Zaluki, Nurwati Ashikkin (Emerald Publishing Limited, 2017)
Purpose: This paper aims to examine the impact of disclosure regulation on the levels of bias and accuracy in management earnings forecasts disclosed in the prospectuses of Malaysian initial public offering (IPO). Specifically, the authors investigated the two environments of regulation (mandatory versus voluntary) to draw some conclusions regarding the benefits of regulating disclosure of management earnings forecasts. Design/methodology/approach: A sample of 111 Malaysian IPOs listing on the Main Market of Bursa Malaysia from January 1, 2004 to February 29, 2012 was used. The paper uses both univariate and multivariate statistical analyses on this sample of IPOs.Findings: The empirical results of these multivariate regressions indicated that disclosure regulation has positive and significant impact on the bias and accuracy of management earnings forecasts disclosed in IPO prospectus. In general, the study results suggest that using disclosure regulation to improve the quality of IPO earnings forecasts can be, to some extent, an effective strategy.